Pewarnaan Alami Benang Katun Menggunakan Angkak (Monascus Purpureus) - Yuditira, Syafira Tasya; Santoso, Ratna Endah (Universitas Negeri Surabaya, 2023)
Natural dyes can be obtained from plants, animals, minerals, and microorganisms. The microorganism that has the ability to produce pigment is Monascus Purpureus. Angkak, or Monascus purpureus, is the result of the fermentation of rice with the mushroom Monascus Sp. Monascus purpureus mushrooms can produce large amounts of carotenoid pigment, resulting in a red colour. Angkak is often used as a traditional medicine, a food base, and especially as a natural food colourant. However, the knowledge and application of natural dyeing for textiles are still very rare, especially on cotton yarn. This research refers to experimental methods carried out based on data collection in the form of literary studies, trials, observations, and interviews. The process of natural colouring cotton ropes with angkak is carried out in several stages and using several techniques. The natural colouring of the cotton yarn produces varying nude colours. The study resulted in 16 colour variations of 16 combinations of mordant and fixation materials. The results of this study can provide more insight into the natural colouring potential of cotton, thus making it an environmentally friendly and sustainable textile colouring alternative in the textile industry.